Medidas executivas atípicas: análise crítica sobre a relevância e aplicação do artigo 139, inciso IV do Código de Processo Civil para a efetividade da prestação jurisdicional na obrigação de pagar quantia certa - Madeira, Bruno da Silva (2019)
The purpose of this paper is to analyze the introduction of article 139, IV by the Code of Civil Procedure promulgated in 2015, which deals with atypical executive measures, drawing a rationale of its application in the context of attempting to solve the problem of the effectiveness of the jurisdictional provision of the executive tutelage. First, we deal with the executive means and its field of incidence - execution and enforcement process. Next, there is an analysis of the guarantee of the effectiveness of the jurisdictional rendering, under its various prisms, with considerations about its problematic in Brazil and in foreign countries. Afterwards, the atypical executive measures set forth in article 139, IV of the CPC are analyzed, their correct application by magistrates and their importance for such effectiveness. Finally, the constitutionality of the application of atypical measures is highlighted, respecting certain limits and parameters, already delineated by the Doctrine and Jurisprudence and here summarized